Sports career termination in football players: systematic review - Carapinheira, António (2019)
This article aimed to characterize the termination of the sports career in football players. A systematic literature search was performed according to the PRISMA method. From all the publications, eight were selected that fulfilled all the inclusion criteria. The results revealed that, in general, the former football players finish their career between the ages of 31 and 35, reported a career span between eight and eleven years, and secondary education level. Regarding the quality of retirement, it was reported that voluntary retirement was mainly due to age and associated with psychological and social problems. Few data were reported regarding the available resources, highlighting, however, coping strategies through support from family and friends, and players maintain a career linked to sports. Only one study revealed the existence of a program to support the retirement of a sports career. © 2018, Facultad de Formacion del Profesorado.